Avaliações (socio)linguísticas sobre os pronomes pessoais de segunda pessoa do singular na fala de maranhenses - LOPES, João Vitor Cunha (2023)
This master thesis, based on the theoretical and methodological assumptions of Variationist Sociolinguistics (Weinreich, Labov, Herzog, 2006 [1968]; Labov, 2006 [1966]; 2008 [1972]; Eckert, 2012; Oushiro, 2015, among others), proposes to analyze metacomments about the Maranhão dialect, in order to access what sociolinguistic evaluations emerge from the discourse of speakers in relation to the discourse that maranhense speak the best variety of Brazilian Portuguese, focusing on the linguistic variable the second-person subject pronoun in singular, especially the realization of the subject pronoun you "tu", popularly considered as a peculiar characteristic of the Maranhão dialect, responsible, to some extent, for the maintenance of the discourse that maranhense speaks the best Portuguese, alongside the subject pronoun you "você", which shows a growing use among the ludovicenses (Alves 2010, Carneiro, 2011). Initially, an analysis of audio and transcripts of sociolinguistic interviews that make up two samples of speech was carried out: ludovicense and bacabalense. The ludovicense sample was built by Santos (2015), while the bacabalense sample was built by Lopes (2019). The results of this analysis showed that the bacabalenses did not present many metacomments so explicit about their own way of speaking. On the other hand, the ludovicenses, relatively to the bacabalenses, were much more productive when it comes to presenting metacomments about their own way of speaking and showed, to some extent, the belief that maranhenses and, especially the ludovicenses, speak the best Portuguese in Brazil. In addition, they presented the use of the pronoun you "tu" as a ludovicense mark. Some, even, presented a negative assessment of the use of the pronoun you "você". Based on the initial analysis of these sociolinguistic interviews, it was proposed to build a sample of sociolinguistic assessments of bacabalenses, for the purpose of complementing the bacabalense sample and comparing it with the ludovicense sample. In this sense, a semi-structured interview script was developed that could elicit metacomments about the Maranhão dialect, about some linguistic variables, in order to verify if, from these metacomments, discourses emerge about the way maranhenses speak. The analyses of these last interviews revealed that, when more directly prompted about the discourse of the overvaluation of the Maranhão Portuguese, the bacabalenses present a positive assessment of this discourse, as well as the ludovicenses. However, on the use of subject pronouns, even though the use of the subject pronoun you "tu" has been considered as normal among the bacabalenses, there is a slight advantage of the positive assessment of the use of the subject pronoun you "você". Finally, by comparing the sociolinguistic assessments of ludovicenses and bacabalenses, this work contributes to the expansion of the sociolinguistic description of the maranhense portuguese, especially in the sense of presenting how maranhenses assess their own variety.